2013
DOI: 10.4049/jimmunol.1300864
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA Induces Tolerogenic Dendritic Cells through SIGNR1 Dampening Autoimmunity in Mice

Abstract: IgA plays ambivalent roles in the immune system. The balance between inhibitory and activating responses relies on the multimerization status of IgA and interaction with their cognate receptors. In mucosal sites, secretory IgA (SIgA) protects the host through immune-exclusion mechanisms, but its function in the bloodstream remains unknown. Using bone marrow–derived dendritic cells, we found that both human and mouse SIgA induce tolerogenic dendritic cells (DCs) following binding to specific ICAM-3 grabbing non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…the cell surface receptor SIGNR1, 155 suggesting that while these cells provide effective protection at mucosal barriers, they may co-provide regulatory functions to prevent excessive inflammation. Putative functions of PC and IgA C PC in particular are depicted in Figure 2.…”
Section: Plasma Cells As a Source Of Cytokinesmentioning
confidence: 99%
“…the cell surface receptor SIGNR1, 155 suggesting that while these cells provide effective protection at mucosal barriers, they may co-provide regulatory functions to prevent excessive inflammation. Putative functions of PC and IgA C PC in particular are depicted in Figure 2.…”
Section: Plasma Cells As a Source Of Cytokinesmentioning
confidence: 99%
“…The recent observation that immunoregulation of DCs by SIgA is potent in inhibiting autoimmune responses in mouse models suggest that the antibody is important to establish healthy homeostasis and possibly to serve in disease prevention. 62 The importance of SIgA to ensure optimal immune maturation and to support long-term gut homeostasis was recently further supported in a totally different experimental model. Indeed, exploiting a mother foster approach with pIgR-sufficient and deficient mice, whose milk either contains or was devoid of SIgA, respectively, it was demonstrated that early exposure to maternal breast milk SIgA promoted intestinal epithelial barrier function.…”
Section: Effect Of Siga On Commensal-bacteriadriven Early Maturation mentioning
confidence: 99%
“…Further studies led to identify the relevance of IgA receptors (IgA-R) in the deposits. Several IgA-Rs have been recognized [78][79][80] . In the IgAN pathogenesis, two IgA-R expressing cells have been principally involved: (1) mesangial cells which have been documented to be implicated in kidney injury; and (2) myeloid cells (essentially kidney infiltrating macrophages) which have been documented to modulate the extent of the inflammatory response.…”
Section: Salvadori M Et Al Pathophysiology Of Nephropathymentioning
confidence: 99%